Further investigation of perturbations in FLRW space-time - Dhungel, Prem Raj; Sharma, Sanat Kumar; Khanal, Uday Raj (Scientific World, 2024)
The solutions of perturbation equations in FLRW spacetime were further analysed for indications of structure formation. The radial and angular parts of the wavefunction reveal various possibilities of spatial and angular sizes in terms of quantum numbers ω, k, l and m. They offer slightly contrasting results for the three cases of the closed, open and flat universes including for each of all the 3 modes of perturbations – scalar, vectorial and tensorial. It is seen that the structures of large scales are more compact in the closed case, slightly diffuse in the flat one. Also structures of different sizes are more probable in the open case.